Efficacy of pirfenidone vs. placebo in unclassifiable interstitial lung disease, by surgical lung biopsy status: data from a post-hoc analysis - Molina-Molina, Maria; Kreuter, Michael; Cottin, Vincent; Corte, Tamera J.; Gilberg, Frank; Kirchgaessler, Klaus-Uwe; Axmann, Judit; Maher, Toby M. (Frontiers in medicine, 2022)
Approximately 12-13% of patients with interstitial lung disease (ILD) are diagnosed with unclassifiable ILD (uILD), often despite thorough evaluation. A recent Phase 2 study (NCT03099187) described a significant effect of pirfenidone vs. placebo on forced vital capacity (FVC) measured by site spirometry in patients with progressive fibrosing uILD (hereafter referred to as the pirfenidone in uILD study). Here, we present the results from a post-hoc analysis of this study to assess patient baseline characteristics and the efficacy of pirfenidone vs. placebo analyzed by surgical lung biopsy (SLB) status. Mean FVC (mL) change over 24 weeks was included as a post-hoc efficacy outcome. Of 253 randomized patients, 88 (34.8%) had a SLB and 165 (65.2%) did not. Baseline characteristics were generally similar between SLB subgroups; however, patients who had a SLB were slightly younger and had a higher 6-min walk distance than those without a SLB. Mean FVC change over 24 weeks for pirfenidone vs. placebo was −90.9 vs. −146.3 mL, respectively, in patients who had a SLB, and 8.2 vs. −85.3 mL, respectively, in patients without a SLB. Overall, the results from the post-hoc analysis identified that pirfenidone may be an effective treatment in progressive fibrosing uILD over 24 weeks, irrespective of SLB status; however, caution should be taken when interpreting these data due to several limitations. There are differences in the treatment effect of pirfenidone between the subgroups that require further pathological and radiological investigation. In this manuscript, we also descriptively compared baseline characteristics from the overall pirfenidone in uILD study population with other uILD populations reported in the literature, with the aim of understanding if there are any similarities or differences within these cohorts. Most baseline characteristics for patients in the pirfenidone in uILD study were within the ranges reported in the literature; however, ranges were wide, highlighting the heterogeneity of uILD populations.Clinical Trial RegistrationClinicalTrials.gov, identifier: NCT03099187.
Gesehen am 29.11.2022